If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(5)(x) = 120 Reorder the terms: (2 + x)(5)(x) = 120 Reorder the terms for easier multiplication: 5x(2 + x) = 120 (2 * 5x + x * 5x) = 120 (10x + 5x2) = 120 Solving 10x + 5x2 = 120 Solving for variable 'x'. Reorder the terms: -120 + 10x + 5x2 = 120 + -120 Combine like terms: 120 + -120 = 0 -120 + 10x + 5x2 = 0 Factor out the Greatest Common Factor (GCF), '5'. 5(-24 + 2x + x2) = 0 Factor a trinomial. 5((-6 + -1x)(4 + -1x)) = 0 Ignore the factor 5.Subproblem 1
Set the factor '(-6 + -1x)' equal to zero and attempt to solve: Simplifying -6 + -1x = 0 Solving -6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 0 + 6 -1x = 0 + 6 Combine like terms: 0 + 6 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Solution
x = {-6, 4}
| 14y-3y=4 | | -6y-2(-6z+6y)+3z= | | 2x+3y=73 | | 6-5x+3x=-18 | | 2n+7=3n-4 | | (5x-6)/(9x-4) | | 5x-6/9x-4 | | 2x+3y+42=7 | | U=2(9n+31)+9(n+1) | | (23-4p)+3= | | -0.5(-.3x-0.6)=-1.5 | | 10-3/4x=1/5 | | 3x+8y=54 | | 10-7/6-2 | | 9x+8.32=5x+13 | | -8-2w=17 | | 15p-15-10p=0 | | 3+4=7x+2 | | t/4.7=-14.7 | | 7-y=12 | | 218.25=39.5w | | y-1=-2/3(x-2) | | 25+20=55+10 | | m/10.1=3.5 | | .35+5=12.70 | | 4c-7=8c-2 | | 3n×m-n/9 | | 2x+3=5.70 | | 9x+17+4x-10=88 | | 4x+25x+10=-1x | | 45-x=82 | | m-(m-n/9) |